Predictive validity of the Scale of Prodromal Symptoms (SOPS) - Lemos, S; Vallina, O; Fernández, P; Ortega, J A; García, P; Gutiérrez, A; Bobes, J; García, A; Miller, T (Actas españolas de psiquiatría, 2006)
We conduct an exploratory factor analysis with the Scale of Prodromal Symptoms (SOPS) items, to determine its psychometric characteristics and construct validity, as well as we analyze criterion or predictive validity of its clinical subscales in the conversion of high mental risk subjects from prodrome to psychosis in a 1 year follow-up period. The subjects were 30 patients referred for evaluation with the Structured Interview of Prodromal Syndromes (SIPS), which includes the SOPS, because of a suspected psychosis prodromal syndrome, a factor analysis with varimax rotation was carried out: Cronbach internal coherence indices were obtained, and predictive validity of the subscales comprising this instrument were analyzed using logistic regression. Three first-order factors were found, one of them was a homogeneous component made up of negative symptoms, consistent with previous studies, and higher scores were observed in negative, disorganized and general symptoms in males. Cronbach's alpha indices were 0.880, in the recruitment phase of risk patients, and 0.952 one year later. With an incidence rate of psychosis of 26.67 % in the sample studied, during the 1 year follow-up period, an excellent positive predictive value of the SOPS subscales was found, with negative symptoms having the best specificity (95.5 %) and sensitivity (100 %) indices. Diagnostic criteria based on the SIPS/ SOPS make it possible to identify persons at high risk of psychosis, and to make an accurate prediction of medium term psychotic episodes. It is a valid, economical and easy to use instrument in primary health care systems.